Spatial-Temporal Oscillations of Relaxation and Pre-Turbulent Type in Ideal Confined Amorphous Alloys - I.B. Krasnyuk; T.N. Melnik; R.M. Taranets; V.M. Yurchenko (Журнал нано- та електронної фізики)
The conditions for oscillating distributions at surface-induced crystallization of a quasi-binary volcanic melt, as a superposition of two travelling waves, are found. It is shown that change in the cooling conditions on the surfaces of flat walls which confine the melt leads to the change in the surface structure, i.e. surface amorphous-crystal waves penetrating the amorphous melt and initiating different types of pulse oscillations in the bulk in turn. For ideal melts, when bulk perturbations can be neglected, the solution tends to an asymptotically periodic piecewise-constant function. In the case of non-ideal melts, competition between surface and volume fluctuations arises and solution tends to an asymptotically quasi-periodic function.